EFEKTIVITAS EKSTRAK BAWANG PUTIH DAN TEMBAKAU TERHADAP KUTU DAUN (MYZUS PERSICAE SULZ.) PADA TANAMAN CABAI (CAPSICUM SP.) - Tigauw, Selviana M.I.; Salaki, Ch. L.; Manueke, J. (Universitas Sam Ratulangi, 2015)
ABSTRACT The research was conducted in the village of Mapanget, Mapanget West District of Manado City for five months from February to June 2015. This study used a factorial design in a completely randomized design (CRD) with two factors was garlic ekstrak and tobacco and repeated for three times. The result showed that each kind of extracts garlic, tobacco and the combination of the two (synergistic) have the potential as the bioinsecticides against leaf aphids (Myzus persicae Sulz.). For a single factor, the average percentage of the highest mortality of each extracts was garlic extract on concentration?s treatment 60% with 72,33% of death rate, tobacco extract on concentration?s treatment 60% with 76,33% of death rate of leaf aphids. As for the combination between garlic extract and tobacco extract, from 25 combinations that have been applied, there are 13 concentrations which effective to known as a bioinsecticide that have capability to caused mortality above 50% with the highest mortality percentage on 60%:60% treatment which had 91,7% average of death rate. Keywords : effectiveness, bioinsecticides, Myzus persicae